2011
DOI: 10.1002/chem.201002798
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Prodrugs Based on the Natural Antibiotic Duocarmycin for Use in ADEPT and PMT

Abstract: Chemotherapy of malign tumors is usually associated with serious side effects as common anticancer drugs lack selectivity. An approach to deal with this problem is the antibody-directed enzyme prodrug therapy (ADEPT) and the prodrug monotherapy (PMT). Herein, the synthesis and biological evaluation of new glycosidic prodrugs suitable for both concepts are described. All prodrugs but one are stable in human serum and show QIC(50) values (IC(50) of prodrug/IC(50) of prodrug in the presence of the appropriate gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…One such prodrug is a duocarmycin SA analog (Tietze et al, 2011), which selectivity binds the N3 of adenine in AT rich-minor DNA groove regions. Duocarmycin SA is one of the strongest known anticancer compounds, but even analogs trigger severe myelotoxicity (Hurley et al, 1988;Puyo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One such prodrug is a duocarmycin SA analog (Tietze et al, 2011), which selectivity binds the N3 of adenine in AT rich-minor DNA groove regions. Duocarmycin SA is one of the strongest known anticancer compounds, but even analogs trigger severe myelotoxicity (Hurley et al, 1988;Puyo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The active moiety or tumor‐associated antigen‐specific monoclonal antibody of ADPET and PMT is efficiently released by the action of specific enzymes expressed at high levels in tumor tissues . It was found that α‐mannosidase activity and β‐galactosidase activity are elevated in certain cancer types, such as breast cancer, gliomas, leukemias, colon cancer, bladder cancer, larynx cancer, and ovarian cancer . The case is similar for l ‐fucosidase activity in breast cancer, leukemia, and ovarian cancer .…”
Section: Targeting Properties Of Mono‐ and Disaccharidesmentioning
confidence: 94%
“…[46] Therefore, carbohydrates, including mono-o rd isaccharides, were incorporated into nonspecific antitumor compounds to improve their specificity and efficacy.The active moiety or tumor-associated antigen-specific monoclonal antibody of ADPET and PMT is efficiently released by the action of specific enzymes expressed at high levels in tumor tissues. [46][47][48] It wasf ound that a-mannosidase activity and b-galactosidasea ctivity are elevated in certain cancer types, such as breast cancer, [49] gliomas, [50] leukemias, [51] colon cancer, [52] bladder cancer, [47] larynx cancer, [53] and ovarian cancer. [54] The case is similar for l-fucosidase activity in breast cancer, [47] leukemia, [55] and ovarian cancer.…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, numerous glucuronide prodrugs (Grinda et al 2011(Grinda et al , 2012Thomas et al 2008;Tietze et al 2011) that can be activated by β-glucuronidase present in the tumor microenvironment (Bosslet et al 1995;Connors and Whisson 1966) have been investigated to enhance the selectivity of cancer chemotherapy. The β-glucuronidase is a lysosomal enzyme released mainly by the immune and inflammatory cells of the necrotic area (Bosslet et al 1998).…”
Section: Introductionmentioning
confidence: 99%